The Influence of 2013 Curriculum Implementation on Teacher Performance - Juliana, Imelia; Ermayani, Ermayani (Jurnal Pendidikan Agama Islam Indonesia (JPAII), 2023)
Purpose of the study: The purpose of this study was to find out how the 2013 curriculum was implemented in high school classes at Madrasah Ibtidaiyah Nahdhatul Ulama II Tembilahan Hulu. To find out how the performance of high school teachers at Madrasah Ibtidaiyah Nahdhatul Ulama II Tembilahan Hulu. To find out how the influence of the implementation of the 2013 curriculum on the performance of high school teachers at Madrasah Ibtidaiyah Nahdhatul Ulama II Tembilahan Hulu. Methodology: This type of research is a quantitative descriptive research. The population in this study were 3 high school teachers at Madrasah Ibtidaiyah Nahdhatul Ulama II Tembilahan Hulu. The data in this study were collected using observation and documentation techniques. Furthermore, the collected data was analyzed using a simple linear regression analysis formula. Main Findings: The implementation of the 2013 curriculum in high grades at Madrasah Ibtidaiyah Nahdhatul Ulama II Tembilahan Hulu, reached 69.57% and was categorized as good, because the 69.57% rate lies in the 61% - 80% interval. The performance of high grade teachers at Madrasah Ibtidaiyah Nahdhatul Ulama II Tembilahan Hulu, reaches 67.28% and is categorized as good, because the 67.28% figure lies in the 61% - 80% interval. There is a positive and significant influence between the implementation of the 2013 curriculum on teacher performance at Madrasah Ibtidaiyah Nahdhatul Ulama II Tembilahan Hulu, which is indicated by the number 80.36 and is interpreted as high. Because based on Ftable , the value for 7 is 5.59. So that Fcount ≥ Ftable, meaning = 80.36 ≥ 5.59, then Ho is rejected, the number 80.36 lies in the acceptance area, then Ha is accepted and Ho is rejected. Novelty/Originality of this study: The update of this research is to see how the influence of the implementation of the 2013 curriculum on teacher performance at the Islamic elementary school Nahdatul Ulama II in Tembilahan Hulu.